1999
DOI: 10.1001/archpsyc.56.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Proton Echo-Planar Spectroscopic Imaging of Brain Metabolic Changes During Lactate-Induced Panic

Abstract: Background: A fast, proton echo-planar spectroscopic imaging (PEPSI) technique, capable of simultaneously measuring metabolites from multiple brain regions, was used to investigate the anatomical distribution and magnitude of brain lactate responses to intravenous lactate infusion among subjects with panic disorder and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…This confirms and extends the findings of prior studies showing elevated brain lactate responses during metabolic challenges in patients with PD. 16,[28][29][30] Increased local oxygen availability, rather than hypoxia, in response to stimulus-induced neural activation is one of the most well-established observations in neuroscience. 44,45 Since the hypoxia model attributes the consistently elevated brain lactate responses observed in PD to ischemic hypoxia, 16,20,21 it predicts that the characteristic elevation of brain lactate would not be observed in the visual cortex in PD patients during visual stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms and extends the findings of prior studies showing elevated brain lactate responses during metabolic challenges in patients with PD. 16,[28][29][30] Increased local oxygen availability, rather than hypoxia, in response to stimulus-induced neural activation is one of the most well-established observations in neuroscience. 44,45 Since the hypoxia model attributes the consistently elevated brain lactate responses observed in PD to ischemic hypoxia, 16,20,21 it predicts that the characteristic elevation of brain lactate would not be observed in the visual cortex in PD patients during visual stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies of sodium lactate infusions and one study of hyperventilation have all observed significantly greater increases in brain lactate in PD patients. 16,[28][29][30] Some investigators proposed that the abnormal lactate response resulted from a disturbance in the dynamics of lactate metabolism in PD, 14 while others attributed it to cerebral hypoxia due to an exaggerated cerebral vasoconstriction response to alkalosis in PD. 16,20,21 It is well known that lactate accumulates under hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a more rapid and substantial rise in brain lactate has been observed in panic patients as compared with control subjects (Dager et al 1999), but the difference between patients and controls may also be due to different responsiveness to a given concentration (Pohl et al 1994;Rifkin et al 1981).…”
Section: In Patients With Panic Disorder or Premenstrual Dysphoria Amentioning
confidence: 99%
“…Clinical neuroscientists have begun to use 1H-MRS measures of brain lactate responses to characterize normal and clinical populations, although the strengths and limitations of this method are not well understood. Elevated brain lactate responses to metabolic challenges have consistently been observed in patients with panic disorder (Dager et al, 1995;Dager et al, 1999;Maddock, 2001), and these findings have recently been extended to include elevated visual cortex lactate responses to visual stimulation (Maddock and Buonocore, 2005). Richards and colleagues reported elevated lactate in left frontal regions in dyslexic boys during an oral language task and later showed normalization with treatment (Richards et al, 2000).…”
Section: Introductionmentioning
confidence: 99%